PEMBERDAYAAN KOPERASI MELALUI VALUE CHAIN UNTUK MENCIPTAKAN KEUNGGULAN BERSAING - Titik Mildawati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The research issue is to know whether value chain analysis can be at cooperation to competitive advantage especially in Duta Niaga Cooperation in Jember or not. Value chain analysis can be with choosing value added activity. Linked Business Units are food supplier, rice milling unit, and transportation unit.The result shows that by choosy are cooperation must buy field dry rice (gabah kering sawah/GKS) in cooperation warehouse especially in harvest, thine and must process being mill dry rice (gabah kering giling/GKG). Also cooperation must use outsourcing transportation service at application of milling contract